2018
DOI: 10.1007/978-3-319-76270-8_45
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Dance Choreography Assistance

Abstract: Creative support for the performing arts is prevalent in many fields, however, for the art of dance, automated tools supporting creativity have been scarce. In this research, we describe ongoing research into (semi)automatic automated creative choreography support. Based on state-of-the-art and a survey among 54 choreographers we establish functionalities and requirements for a choreography assistance tool, including the semantic levels at which it should operate and communicate with the end-users. We describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This is an important criterion in the presentation of national choreographic work because the world of semantic convergence, analogies, and oppositions, which does not coincide with the semantic grid of the natural language of choreography, comes into conflict with it (Tleubayev, 2000). A specific approach to dance segmentation into related fragments has been effectively used for three-dimensional dance modeling and now forms the basis for interactive accompaniment of choreography training and in online dance training systems (de Boer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is an important criterion in the presentation of national choreographic work because the world of semantic convergence, analogies, and oppositions, which does not coincide with the semantic grid of the natural language of choreography, comes into conflict with it (Tleubayev, 2000). A specific approach to dance segmentation into related fragments has been effectively used for three-dimensional dance modeling and now forms the basis for interactive accompaniment of choreography training and in online dance training systems (de Boer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The goal is to help users understand the spatiality of the choreography, as well as its temporality. We motivate the design of a 3D representation of dance movements by the results of the study in [12]. They compared Benesh and Laban notations in a 2D and a 3D animation and found that the 3D animation did not disrupt the dancers and stimulated their creativity, and supported their understanding of the movement better than the 2D animation.…”
Section: Previous Work 21 Dance Notations and Augmented Dance Notationsmentioning
confidence: 99%
“…e above calculation process can get all the angle values except the two degrees of freedom of the ankle [10]. For the calculation of the angle of the ankle joint, the relative position of the robot and the ground needs to be taken into consideration because the sole of the foot must be parallel to the ground.…”
Section: Calculation Of the Angle Between The Vector And Thementioning
confidence: 99%